Implementation of 128/256 bit data bus microprocessor core on FPGA - Weng, Fook Lee; Ali Yeon, Md. Shakaff, Prof. Dr. (International Congress for global Science and Technology (ICGST), 2011)
Link to publisher's homepage at http://www.icgst.com